URGENSI PENGUATAN PERAN KOMISI YUDISIAL DALAM MELAKUKAN PENGAWASAN HAKIM DI INDONESIA - Jasmi, Muhammad; Suasono, Edy (Tanjungpura Legal Review, 2023)
AbstractThe Judicial Commission was born in the reform era when the third amendment to the 1945 Constitution of the Republic of Indonesia in 2001 coincided with the Regional Representative Council and the Constitutional Court, although the Judicial Commission is a new institution, its existence has very strong legal justification because it is strictly regulated in the Law. The 1945 Constitution of the Republic of Indonesia and its authority are granted by the constitution, so that it has a very strong position. However, the authority of the Judicial Commission tends to be incomplete because it still requires further action from other institutions. For example, in the selection of candidates for Supreme Court justices, the Judicial Commission has the duty and authority to propose candidates for Supreme Court justices. However, in the end the Judicial Commission's proposal was still rejected by the People's Representative Council (DPR). In practice, the House of Representatives (DPR) once disapproved of names proposed from the selection results of the Judicial Commission, even though a number of prominent community figures were involved in the selection process.Based on the above, the research method in this study is normative legal research. Normative legal research is legal research conducted by examining literature or secondary data. In addition to using library materials, this research also uses a statutory approach. The statutory approach (statute approach) is usually used to examine statutory regulations which in their norms still lack or even foster deviant practices both at the technical level and in practice in the field.The conclusion obtained in this study is that the Judicial Commission is a state institution mandated by the 1945 Constitution which has the authority to maintain and uphold the dignity, honor, nobility and also the behavior of judges. The Judicial Commission as a State institution whose duties are related to judicial power which is "Authorized to propose the appointment of Supreme Court Justices and other authorities in the context of protecting and upholding the honor, dignity and behavior of judges". The Judicial Commission in Indonesian constitutional law needs to be strengthened immediately. This is because the existence of the Judicial Commission has a strong position as a judge supervisory institution. Therefore, strengthening the authority of the Judicial Commission must be stated in the 5th amendment to the 1945 Constitution.    Abstrak  Komisi Yudisial lahir pada era reformasi saat amandemen ke III Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 pada tahun 2001 bersamaan dengan Dewan Perwakilan Daerah dan Mahkamah Konstitusi, walaupun Komsi Yudisisal adalah lembaga baru, namun keberadaannya mempunyai justifikasi hukum yang sangat kuat karena diatur secara tegas dalam Undang-Undang Dasar Negara Republik Indonesia 1945 dan kewenanganya diberikan oleh konstitusi, sehingga mempunyai kedudukan yang sangat kuat. Namun kewenangan Komisi Yudisial cenderung tidak sekali selesai karena masih membutuhkan tindakan lanjutan dari lembaga lain. Misalnya, dalam seleksi calon hakim agung, Komisi Yudisial bertugas dan berwenang mengusulkan calon hakim agung. Namun pada akhirnya usulan Komisi Yudisial masih dapat ditolak oleh Dewan Perwakilan Rakyat (DPR). Prakteknya, Dewan Perwakilan Rakyat (DPR) pernah tidak menyetujui nama-nama yang diusulkan dari hasil seleksi Komisi Yudisial meskipun dalam proses seleksi itu telah diikutsertakan sejumlah tokoh masyarakat terkemuka.  Berdasarkan hal diatas, metode penelitian pada penelitian ini adalah penelitian hukum normatif. Penelitian hukum normatif merupakan penelitian hukum yang dilakukan dengan cara meneliti bahan pustaka atau data sekunder. Selain menggunakan bahan-bahan kepustakaan, penelitian ini juga menggunakan pendekatan perundang-undangan (statute approach). Pendekatan perundang-undangan (statute approach) biasanya di gunakan untuk meneliti peraturan perundang-undangan yang dalam penormaannya masih terdapat kekurangan atau malah menyuburkan praktek penyimpangan baik dalam tataran teknis atau dalam pelaksanaannya dilapangan. Kesimpulan yang didapatkan dalam penelitian ini ialah Komisi Yudisial merupakan lembaga negara yang diamanatkan oleh Undang-Undang Dasar 1945 yang memiliki wewenang dalam menjaga dan menegakan suatu martabat, kehormatan, keluhuran dan juga perilaku hakim. Komisi Yudisial sebagai lembaga Negara yang tugasnya berkaitan dengan kekuasaan kehakiman yang "Berwenang mengusulkan pengangkatan Hakim Agung dan wewenang lain dalam rangka menjaga dan menegakan kehormatan, martabat serta perilaku hakim". Komisi Yudisial dalam hukum ketatanegaraan Indonesia perlu diperkuat dengan segera. Hal ini dikarenakan keberadaan Komisi Yudisial memiliki kedudukan yang kuat sebagai lembaga pengawas hakim. Maka dari itu penguatan kewenangan Komisi Yudisial harus tercantum dalam amandemen ke-5 UUD Tahun 1945.